Next of kin’s quality of life before and after implementation of a knowledge-based palliative care intervention in nursing homes - Bökberg, Christina (Qual Life Res, 2019)
PURPOSE: The purpose of this study was to evaluate whether an educational palliative care intervention improved the quality of life for next of kin to older persons in nursing homes. METHODS: Altogether, 90 next of kin in the intervention group and 105 next of kin in the control group were included. Data were collected using the WHOQOL-BREF questionnaire, answered before and 3 months after the intervention was completed. Descriptive and comparative analyses were performed. RESULTS: This study found a statistically significant increase in the Physical health subscale in the intervention group but not in the control group. In contrast, the General health score decreased in the control group but not in the implementation group. Furthermore, we found an increase in the item able to perform activities of daily living in the intervention group and a decrease in the item energy and fatigue in the control group. CONCLUSION: The results indicated small statistical changes regarding next of kins’ QoL in favour of the intervention. Lessons learned from the study for future research are to include next of kin as participants at meetings about next of kin and to include more meetings about the theme next of kin. Both approaches would bring a stronger focus on the family-centred care aspect of the intervention into the education component, which this study indicates the need for. TRIAL REGISTRY: Trial registration NCT02708498. Date of registration 26 February 2016.